2013
DOI: 10.12659/msm.883932
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of maternal serum levels of endothelial nitric oxide synthase, asymmetric dimethylarginine, and homocysteine in normal and preeclamptic pregnancies

Abstract: BackgroundThe aim of this study was to determine the maternal serum concentrations of eNOS, ADMA, and homocysteine in preeclamptic pregnancies.Material/MethodsThe study was carried out on 62 patients with pregnancy complicated by early onset and 53 patients with late onset preeclampsia. The control group consisted of 65 healthy normotensive pregnant patients. The serum eNOS, ADMA and homocysteine concentrations were determined using ELISA assays.ResultsOur study revealed elevated levels of homocysteine and ADM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 43 publications
3
9
2
Order By: Relevance
“…The low NO ∙ levels observed in preeclampsia compared to healthy normotensive pregnancy in this study could be as a result of the endogenous inhibition of eNOS by ADMA. Consistent with previous findings [ 17 , 23 , 29 32 ], this study reports elevated ADMA in preeclamptic women ( Table 1 ). Other studies [ 33 35 ], however, observed unchanged ADMA levels in preeclamptic women compared to normotensive pregnancy.…”
Section: Discussionsupporting
confidence: 93%
“…The low NO ∙ levels observed in preeclampsia compared to healthy normotensive pregnancy in this study could be as a result of the endogenous inhibition of eNOS by ADMA. Consistent with previous findings [ 17 , 23 , 29 32 ], this study reports elevated ADMA in preeclamptic women ( Table 1 ). Other studies [ 33 35 ], however, observed unchanged ADMA levels in preeclamptic women compared to normotensive pregnancy.…”
Section: Discussionsupporting
confidence: 93%
“…Results obtained through statistical analysis showed the incidence of EOPE occured earlier. The findings did not fit when compared to previous studies that said that the EOPE occured in pregnancy < 34 week [10]- [13]. Shallow trophoblast invasion and spiral artery remodeling disorder is a fundamental pathophysiology of the EOPE.…”
Section: Discussioncontrasting
confidence: 98%
“…Preeclampsia can occur ≥34 weeks pregnancy or can be called a late onset preeclampsia (LOPE) [10]- [13]. However, approximately 10% of cases of PE occur <34 week of pregnancy so-called early-onset preeclampsia (EOPE).…”
Section: Introductionmentioning
confidence: 99%
“…The ADMA that accumulates in HHcy results in uncoupling of eNOS, reducing levels of NO and impairing NO bioavailability. 30 Further products of peroxynitrite would induce endothelial dysfunction and thrombogenesis. Moreover, peroxynitrite in turn may cause further uncoupling of NOS.…”
Section: Discussionmentioning
confidence: 99%